2018
DOI: 10.1177/1120672118785280
|View full text |Cite
|
Sign up to set email alerts
|

The RELIEF study: Tolerability and efficacy of preservative-free latanoprost in the treatment of glaucoma or ocular hypertension

Abstract: Preservative-free latanoprost has at least the same intraocular pressure-lowering efficacy as benzalkonium chloride-latanoprost, with a better tolerability profile. This may translate into greater control of treatment and improved quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…Uusitalo et al have demonstrated a decrease in the occurrence of irritation/burning/stinging, foreign body sensation, tearing, itching, dry eye sensation, blepharitis, corneal/conjunctival fluorescein staining 12 weeks after changing therapy from preserved latanoprost to preservative-free tafluprost [2]. Similar results were received by the RELIEF study in which the tolerability and efficacy following a switch from BAC-preserved latanoprost to preservative-free latanoprost were assessed [3].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Uusitalo et al have demonstrated a decrease in the occurrence of irritation/burning/stinging, foreign body sensation, tearing, itching, dry eye sensation, blepharitis, corneal/conjunctival fluorescein staining 12 weeks after changing therapy from preserved latanoprost to preservative-free tafluprost [2]. Similar results were received by the RELIEF study in which the tolerability and efficacy following a switch from BAC-preserved latanoprost to preservative-free latanoprost were assessed [3].…”
Section: Discussionmentioning
confidence: 81%
“…This implicates minimization of the side effects of the treatment [1]. However, prostaglandin F2α analogs (PGAs), which are the first-line eye drops used in primary open-angle glaucoma (POAG), commonly cause local side effects such as burning, stinging, foreign body sensation, tearing, or conjunctival hyperemia, especially in patients undergoing long-term treatment [2,3]. These adverse effects not only reduce the quality of life but are also responsible for treatment cessation by the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Bulbar conjunctival hyperemia and corneal/conjunctival were found to improve by using PF eye drops in our study as well as in other studies. Our research team and Misiuk-Hojlo et al [ 16 ] reported no improvement in tear breakdown time, while others reported significantly improved results [ 8 , 20 , 22 ]. The OSDI was significantly decreased in our study, and a previous study [ 20 ] presented similar results.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, there have been efforts to develop PF anti-glaucoma eye drops. In addition, studies comparing the effects of PF eye drops and conventional eye drops have been conducted in various countries [ 8 , 16 , 18 22 ]. In most studies, the effects of both eye-drops on IOP were similar, but PF eye drops tended to be more effective in reducing ocular surface symptoms and signs.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, PF-tafluprost should be especially beneficial for patients with preexisting OSD. Several studies found that PF-latanoprost had an equivalent IOP-reducing efficacy compared to PC-latanoprost, although it was better tolerated [55,61]. Preservative-free eyedrops could possibly be the future development tendency for antiglaucoma drugs.…”
Section: Discussionmentioning
confidence: 99%